2005
DOI: 10.1111/j.1365-2591.2005.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different types of automated devices on the shaping ability of rotary nickel‐titanium FlexMaster instruments

Abstract: All systems respected original root canal curvature well and were safe, indicating that torque-limited rotation handpieces are suitable for preparing curved root canals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Several automated devices have been developed including electric high‐ and low‐torque control motors (Gambarini 2000, 2001, Hülsmann et al. 2005) and torque‐limited rotation handpieces (Yared & Sleiman 2001, Dammaschke & Schäfer 2004, Schäfer et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several automated devices have been developed including electric high‐ and low‐torque control motors (Gambarini 2000, 2001, Hülsmann et al. 2005) and torque‐limited rotation handpieces (Yared & Sleiman 2001, Dammaschke & Schäfer 2004, Schäfer et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2005). In a previous study it has been shown that both electric low‐torque control motors and torque‐limited air‐driven handpieces are suitable for the preparation of curved canals and were at the same time safe to use (Schäfer et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the data on RaCE instruments probably reflects the various instrument sequences used as well as the different experimental models utilized. Fractures of FlexMaster instruments have also been reported (5,6,20); this indicates that all systems have the potential to fracture, particularly in narrow curved canals. Controlling working length during root canal treatment is essential.…”
Section: Discussionmentioning
confidence: 91%
“…When comparing an Endo IT and SiroNiti angle handpiece, Schäfer et al determined a significantly shorter preparation time when using the Endo IT device [27]. The torque control for triggering the magnetic coupling of the SiroNiti handpiece is mechanical.…”
Section: Preparation Timementioning
confidence: 99%